Oedipus at Colonus - Sophocles; Taylor, Don. (Princeton, N.J. Films for the Humanities and Sciences, 1987)
A play performed by the British classical actors. Oedipus in this play is old and rails against the indignities of old age. He feels himself a man chosen by the gods now, an old man, blind and outcast, he wanders through Greece guided by his daugther Antigone until he comes to Colunus, where he knows he will die. Protected by the ruler of Thebes against the armies of Creon who have come in pursuit. Oedipus curses his sone Polymices for indifference and ingratitude.
Part 1 (58 min.) -- part 2 (1 hr. 13 min.)
VHS.
Keywords: Oedipus (Greek mythology).; Tragedies